Determinants of return on equity: evidence from NASDAQ 100 - Kharatyan, Davit (2017)
This study aims to investigate factors that may affect return on equity (ROE). Firms with higher ROE typically have competitive advantages over their competitors which translates into superior returns for investors. Therefore, it is imperative to study the drivers of ROE, particularly ratios and indicators that may have considerable impact. The analysis is done on a sample of 90 largest nonfinancial companies which are components of NASDAQ-100 index and also on industry sector samples. The ordinary least squares method is used to find the most impactful drivers of ROE. The extended DuPont model’s components are considered as the primary factors affecting ROE. In addition, other ratios and indicators such as price to earnings, price to book and current are also incorporated. According to our findings, the most relevant ratios that determine ROE are tax burden, interest burden, operating margin, asset turnover and financial leverage (extended DuPont components) regardless of industry sectors.